Holistic Reasoning on Quality of Life Dimensions Based on Mobile apps with Ontology - Cavaco, Isabela; Siebra, Clauirton (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2020)
To integrate the information about diverse QoL dimensions and enable the specification of a holistic process of reasoning that can improve the effectiveness of interventions, we explore the integration of different QoL aspects in the form of an ontological model, presenting associations between their concepts that should be considered together when inferences are made, since they are usually intrinsically related and would not be complete when separately analysed. These dimensions will be studied from a selected bundle of iOS and Android mobile apps within QoL aspects of Diet, Emotional,